Molecular evolution of the tprC, D, I, K, G, and J genes in the pathogenic genus Treponema. - Gray, R; Mulligan, C; Molini, B; Sun, E; Giacani, L; Godornes, C; Kitchen, A; Lukehart, SA; Centurion-Lara, A (2006)
We investigated the evolution of 6 genes from the Treponema pallidum repeat (tpr) gene family, which encode potential virulence factors and are assumed to have evolved through gene duplication and gene conversion events. The 6 loci (tprC, D, G, J, I, and K) were sequenced and analyzed in several members of the genus Treponema, including the 3 subspecies of human T. pallidum (T. pallidum subsp. pallidum, pertenue, and endemicum), Treponema paraluiscuniculi (rabbit syphilis), and the unclassified Fribourg-Blanc (simian) isolate. Phylogenetic methods, recombination analysis, and measures of nucleotide diversity were used to investigate the evolutionary history of the tpr genes. Numerous instances of gene conversion were detected by all 3 methods including both homogenizing gene conversion that involved the entire length of the sequence as well as site-specific conversions that affected smaller regions. We determined the relative age and directionality of the gene conversion events whenever possible. Our data are also relevant to a discussion of the evolution of the treponemes themselves. Higher levels of variation exist between the human subspecies than within them, supporting the classification of the human treponemes into 3 subspecies. In contrast to published theories, the divergence and diversity of T. pallidum subsp. pertenue relative to the other subspecies does not support a much older origin of yaws at the emergence of modern human, nor is the level of divergence seen in T. pallidum subsp. pallidum consistent with a very recent (< 500 years) origin of this subspecies. In general, our results demonstrate that intragenomic recombination has played a significant role in the evolution of the studied tpr genes and emphasize that efforts to infer evolutionary history of the treponemes can be complicated if past recombination events are not recognized.